Tren Penggunaan Problem-Based Flipped Learning Dalam Pendidikan Abad Ke-21: Systematic Literature Review - Hadi, Mohamad Irsan; Agustini, Ketut; Suartama, I Kadek (Jayapangus Press, 2025)
The transformation of education in the era of the Industrial Revolution 4.0 demands innovative, active, and technology-based approaches. One relevant pedagogical strategy to address this challenge is Problem-Based Flipped Learning (PBFL), which integrates the flipped classroom model with problem-based learning to foster 21st-century skills. This study aims to investigate the publication trends, implementation contexts, challenges, and strategies related to PBFL from 2022 to 2024. A Systematic Literature Review method was employed using the PRISMA protocol, with articles selected from Google Scholar and DOAJ databases. Out of 100 identified articles, 18 met the inclusion criteria and were analyzed thematically. The findings show that PBFL is most frequently implemented in higher education, particularly in science and technology subjects, and is predominantly applied in Southeast Asia. The main implementation challenges include student and teacher readiness, technological infrastructure limitations, and rigid curricular structures. Identified strategies include strengthening the pre-class phase, designing contextual problem-solving activities, utilizing interactive technology, promoting collaborative learning, and conducting ongoing evaluation and reflection. This study provides a comprehensive overview of the potential and challenges of PBFL as an adaptive learning model to support the development of 21st-century competencies across various formal education levels.